Content Validation of a Novel Screening Tool to Identify Emergency Department Patients With Significant Palliative Care Needs. (July 2015) - George, Naomi; Barrett, Nina; McPeake, Laura; Goett, Rebecca; Anderson, Kelsey; Baird, Janette; Hiestand, Brian
Abstract Background The emergency department (ED) is increasingly used by patients with life‐limiting illness. These patients are frequently admitted to the hospital, where they suffer from poorly controlled symptoms and are often subjected to marginally effective therapies. Palliative care (PC) has emerged as the specialty that cares for patients with advanced illness. PC has been shown to reduce symptoms, improve quality of life, and decrease resource utilization. Unfortunately, most patients who could benefit from PC are never identified. At present, there exists no validated screening tool to identify significant unmet PC needs among ED patients with life‐limiting illness. Objectives The objective was to develop a simple, content‐valid screening tool for use by ED providers to identify ED patients with significant PC needs. A positive screen would result in an inpatient PC consultation. Methods An initial screening tool was developed based on a critical review of the literature. Content validity was determined by a two‐round modified Delphi technique using a panel of PC experts. The expert panel reviewed the items of the tool for accuracy and necessity using a Likert scale and provided narrative feedback. Expert's responses were aggregated and analyzed to revise the tool until consensus was achieved. Greater than 80% agreement, as well as meeting Lawshe's critical values, was required to achieve consensus. Results Fifteen experts completed two rounds of surveys to reach consensus on the content validity of the tool. Three screening items were accepted with minimal revisions. The remaining items were revised, condensed, or eliminated. The final tool contains 13 items divided into three steps: 1) presence of a life‐limiting illness, 2) unmet PC needs, and 3) hospital admission. The majority of panelists (86%) endorsed adoption of the final screening tool. Conclusions Use of a modified Delphi technique resulted in the creation of a content‐validated screening tool for identification of ED patients with significant unmet PC needs. Further validation testing of the instrument is warranted.